1997
DOI: 10.1021/om961032r
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Effects of Ring Tilting on Rates of Intramolecular Electron Transfer in Polyalkyl-Substituted Mixed-Valence Biferrocenium Triiodides

Abstract: Relatively minor perturbations caused by Cp ring substituents in a series of mixed-valence biferrocenium cations have pronounced effects on the electronic structure and rate of intramolecular electron transfer. The X-ray structures of 1‘,2‘,1‘‘‘,2‘‘‘-tetrapropylbiferrocene, 1‘,2‘,1‘‘‘,2‘‘‘-tetrabenzylbiferrocene, 1‘,3‘,1‘‘‘,3‘‘‘-tetrapropylbiferrocene, 1‘,3‘,1‘‘‘,3‘‘‘-tetrabenzylbiferrocene, and their corresponding mixed-valence biferrocenium triiodide salts have been determined at 298 K. The rates of intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Indeed, there is great interest in metal–ligand redox and reactivity cooperativity and metallo-ligand mediated electronic coupling between metals in the chemistry community. Despite interest, the application of mixed valency toward exploring the effects of electronically coupled binuclear scaffolds that could be applied to catalysis has been challenging, due to issues of (A) chemical stability in different redox states; (B) establishing clear design criteria for engendering strong coupling, as similar structures often exhibit different coupling strengths as a result of the balance between geometric and electronic factors that lead to coupling; , and (C) designing scaffolds that are modular enough to retain coupling while parametrizing steric and electronic properties to optimize catalysis. Most mixed-valent catalysts capitalize on cooperative effects between metals that have different chemistries in different oxidation states (e.g., using Class I mixed valent structures with little to no delocalization between metals), or otherwise do not well characterize the effect of metal delocalization on reactivity. , However, work in direct metal–metal interactions between ferrocene and d 0 metals has revealed promising electronic structures and catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is great interest in metal–ligand redox and reactivity cooperativity and metallo-ligand mediated electronic coupling between metals in the chemistry community. Despite interest, the application of mixed valency toward exploring the effects of electronically coupled binuclear scaffolds that could be applied to catalysis has been challenging, due to issues of (A) chemical stability in different redox states; (B) establishing clear design criteria for engendering strong coupling, as similar structures often exhibit different coupling strengths as a result of the balance between geometric and electronic factors that lead to coupling; , and (C) designing scaffolds that are modular enough to retain coupling while parametrizing steric and electronic properties to optimize catalysis. Most mixed-valent catalysts capitalize on cooperative effects between metals that have different chemistries in different oxidation states (e.g., using Class I mixed valent structures with little to no delocalization between metals), or otherwise do not well characterize the effect of metal delocalization on reactivity. , However, work in direct metal–metal interactions between ferrocene and d 0 metals has revealed promising electronic structures and catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Under this lens, mixed valency provides an opportunity to explore chemical space in noninnocent ligand catalysis while capitalizing on well-characterized electronic structures, synthetic strategies, and established theoretical frameworks. Nevertheless, such systems are challenging to create in a reliable, modular way, and the chemical space explored remains insufficient to deduce general principles. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…We suggested that the zero-point energy difference plays a crucial role in determining the nature of the intramolecular electron-transfer rate in biferrocenium cation. Finally, to study the influence of the alkyl substituents on the Cp ring, we prepared a series of polyethylbiferrocenium triiodide 5 and 6 [22]. We found that the deviations of the Cp rings from the parallel position correlate quite well with the Mo ¨ssbauer transition temperature of electronic delocalization-localiza- tion in mixed-valence biferrocenium cations.…”
Section: Introductionmentioning
confidence: 97%
“…As opposed to closed ferrocenium [8][9][10], ESR spectra of the halfopen and open ferrocenium ions can be observed at room temperature [7]. In connection with our investigations on the electron transfer in mixed-valence biferrocenium cations [11], we became interested in the synthesis of binuclear half-open ferrocene (1).…”
Section: Introductionmentioning
confidence: 99%